Sex work abolitionism and hegemonic feminisms: Implications for gender-diverse sex workers and migrants from Brazil. Issue 4 (July 2020) - Stabile, Lua da Mota
This article investigates and analyses the main characteristics and issues involving Western hegemonic feminisms, especially so-called 'radical feminism', on the topic of sex work and trafficking in persons/migration, to understand how these discussions have influenced the main conventions, regulations and legislation on this global subject. In particular, it enables understanding of how these regulations invisibilize and, sometimes, criminalize trans* and gender-diverse people in migratory contexts. The contributions to decolonial feminism and transfeminism made by decolonial trans writers are essential to analyse and critique some of the conceptions espoused by Western hegemonic and especially trans-exclusionary feminisms that have influenced the international anti-trafficking and anti-prostitution discourse today. These discourses often affect the voluntary migration of trans* and gender-diverse sex workers, mainly from the Global South, such as in the Brazilian case.